Corporate Digital Responsibility Framework for Successful AI Implementation in News Media - Arief Adi Wibowo; John Tampil Purba (Jurnal Ilmiah Manajemen Kesatuan, 2026)
This study aims to identify the key components of Corporate Digital Responsibility (CDR) that are most relevant to AI implementation in news media organizations and to examine the relationships between these dimensions and the mediating factors that shape implementation outcomes. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling to test a framework that integrates digital ethics, responsible innovation, and media sustainability with media credibility, operational effectiveness, and business sustainability as mediating variables toward AI implementation success. The findings indicate that CDR dimensions play a significant role in strengthening credibility, improving operational performance, and supporting long-term business sustainability, which collectively contribute to more effective AI implementation. The results highlight that ethical governance, innovation capability, and sustainability orientation not only influence AI adoption directly but also operate through key organizational mechanisms that enhance trust, efficiency, and resilience. These findings imply that news media organizations need to adopt an integrated and balanced approach to digital responsibility in order to ensure that AI integration supports both technological advancement and journalistic values while maintaining long-term organizational viability.